Mind over mind : the surprising power of expectations - Berdik, Chris (Current, 2012)
How our fast-forward minds make something out of nothing. From a healing placebo to a run on the bank, the self-fulfilling potential of expectations has been observed for years. But now neuroscientists and psychologists are beginning to solve the mysteries of our expectant brain and applying their findings to field ranging from medicine to sports to education. Mind over Mind explores the frontiers of expectations research, revealing how our brains work in the future tense and how our assumptions bend reality. It shows how expectations can sometimes make us healthier, stronger, smarter, and more successful while other times leave us depressed and defeated.--Publisher information.